Educational change: A proposal for a subjective theories transformation model - Cuadra-Martínez, David (2018)
The aim of this paper is to analyze and systematize subjective change in education based on a review of the main contributions derived from national and international studies on subjective theories (ST) conducted to date in the field of education. An overview of the research on ST in education is presented. Findings are then analyzed and systematized in a model of ST change in educational contexts that considers: (a) a paradigmatic framework, (b) a change process, (c) change factors, and (e) change indicators. In the conclusion section, a summary of the process of ST change in educational contexts is proposed, based on empiric studies reviewed and testable in future research, and the limitations that must be overcome in order to make strides in the construction of a theory of ST change in education are discussed.